Food Culture and Ancestral Beliefs in Pregnant Women of the Asháninka Community of Otari-Pichari, Cusco - Maquera-Maquera, Yuselino; Zegarra-Ugarte, Soledad Jackeline; Calderón-Torres, Alfredo; Apaza-Ticona , Jorge; Sardón-Huayapa, Julio César; Alanoca-Arocutipa, Vicente; Ramos-Lopez, Juan (Journal of Ecohumanism, 2024)
This study explores the dietary practices and beliefs of pregnant women in the Asháninka community of Otari-Pichari, highlighting their relevance in shaping cultural identity and maternal and child health. Using a qualitative ethnographic approach, data were collected through interviews and participant observation, revealing that the gestational diet includes local foods, such as yuca, sweet potato, and fish, while others, such as chili, coconut, and snake, are prohibited due to perceived risks to the baby’s development. These choices are deeply rooted in ancestral beliefs that regulate dietary decisions and reinforce social cohesion. The study identifies tensions between local traditions and modern medicine, highlighting the need to implement public health interventions that respect traditional knowledge and foster intercultural dialogue to improve maternal and child well-being. In conclusion, these practices reflect the importance of preserving ancestral knowledge as an integral part of health care and strengthening indigenous communities.